Polityka pamięci a sprawa polska Między nami dobrze jest Doroty Masłowskiej - Gębala, Anna (Śląskie Studia Polonistyczne, 2017)
The author refers to Memory Studies and analyzes the way in which Dorota Masłowska depicts Polish society that took part in the democratic transition 1989–1990. Masłowska puts emphasis on the mechanisms of late capitalism that shape both imaginary ideas and real social structures. The literary representation of the nation points to a community constructed not upon the tradition and history but on the simulacra produced by politically inclined discourse of media, pop culture and consumerism. This outlook offers an interesting point of departure for analyses of social and political changes (especially those following the transition in 1989 and the symbolic politics adopted in that time) mediated by literature. Levels and contexts depicted in the article represent a range of influences, relations, borrowings, persuasion and narratives that accompanied by memory work shape social and individual identities of contemporary Poles.